The influence of an 11-week resisted swim training program on the inter-arm coordination in front crawl swimmers - Valkoumas, I.; Gourgoulis, V.; Aggeloussis, N.; Antoniou, P. (Sports Biomechanics, 2023)
The purpose was to assess the effect of an 11-week resisted swim training program using a water parachute on the inter-arm coordination in front crawl swimming. Fourteen female swimmers were divided into a control and an experimental group, and followed the same training program, except for the use of a water parachute by the experimental group in specific sprint sets. Before and after the intervention, the underwater motion of the swimmers was recorded using four camcorders and the digitisation process was undertaken manually. The two-way repeated measures analyses of variance revealed a significant increase of the swimming velocity, due to a significant increased stroke rate, because of the significant reduction of the total stroke duration, only in the experimental group. Moreover, their absolute and relative duration of the propulsive pull and push phases increased significantly, while the absolute and relative duration of their non-propulsive entry & catch and recovery phases decreased significantly. These modifications caused a significant increase in the index of coordination. Thus, this 11-week sprint resisted intervention program seems to improve the propulsion continuity and could be considered as an effective form of training, increasing the stroke rate and consequently the swimming velocity.